The "Cotton Problem" - Baffes, John (Oxford University Press on behalf of the World Bank, 2013)
Cotton is an important cash crop in many developing economies, supporting the livelihoods of millions of poor households. In some countries it contributes as much as 40 percent of merchandise exports and more than 5 percent of gross domestic product (GDP). The global cotton market, however, has been subject to numerous policy interventions, to the detriment of nonsubsidized producers. This examination of the global cotton market and trade policies reaches four main conclusions. First, rich cotton-producing countries should stop supporting their cotton sectors; as an interim step, transfers to the cotton sector should be fully decoupled from current production decisions. Second, many cotton-producing (and often cotton-dependent) developing economies need to complete their unfinished reform agenda. Third, new technologies, especially genetically modified seed varieties, should be embraced by developing economies; this will entail extensive research to identify varieties appropriate to local growing conditions and the establishment of the proper legislative and regulatory framework. Finally, cotton promotion is needed to reverse or at least arrest cotton s decline as a share of total fiber consumption.